Mathematical Communication Ability in terms of Student Learning Styles in Inquiry Based Learning Assisted by Module - Kurniawati, Fita; Suyitno, Hardi; Mulyono, Mulyono (Unnes Journal of Mathematics Education Research, 2021)
The purpose of this study is to describe mathematical communication ability in terms of student learning styles in module-assisted Inquiry Based Learning. This study uses a combination method of concurrent embedded design with a population of class VIII students of SMP Negeri 1 Jati Kudus and the research sample is based on cluster random sampling. Data collection techniques in this study were observation, mathematical communication ability tests, learning style questionnaires and interviews. The results showed (1) students with visual learning styles were able to write mathematical ideas into mathematical models, compose and explain completion procedures, (2) students with auditory learning styles were able to express everyday events in mathematical language or symbols, write mathematical ideas into in mathematical models, compiling and explaining completion procedures and (3) students with kinesthetic learning styles are able to write mathematical ideas into mathematical models and develop completion procedures.